Design e inovação social: edição de uma fanzine abordando o consumismo e a conscientização dos seus impactos ambientais em busca de uma conduta de consumo e descarte responsáveis - Fontoura, Gabriela Garcia [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
Faced with environmental depreciation, this project reflects on the consumption society, capitalism and its unsustainability. Through the investigation of alternative solutions of consumption and the design of a graphic language, we seek to collaborate in the transition from a culture of unbridled consumerism to a consumption of conscious and sustainable consumption according to the capacity of the resources of planet earth. Having as a practical result, based on the concepts of permaculture, the development of a fanzine in order to promote the popularization of a minimalist conduct and conservation of nature.

Diante da depreciação ambiental, este projeto faz uma reflexão sobre a sociedade do consumo, o capitalismo e sua insustentabilidade. Busca-se, através da investigação de soluções alternativas de consumo e do design de uma linguagem gráfica, colaborar na transição de uma cultura de consumismo desenfreado para uma de consumo consciente e sustentável de acordo com a capacidade dos recursos do planeta terra. Tendo como resultado prático, baseado nos conceitos da permacultura, o desenvolvimento de uma fanzine a fim de promover a popularização de uma conduta minimalista e de conservação da natureza.
Design and social innovation: edition of a fanzine addressing consumerism and awareness of its environmental impacts in search of responsible consumption and disposal behavior
Keywords: Consumerism; Sustainable consumption; Consumismo; Consumo sustentável; Fanzine